2020
DOI: 10.1002/cptc.202000036
|View full text |Cite
|
Sign up to set email alerts
|

Smart Fluorescence Materials that Are Controllable by Hydrostatic Pressure: Peptide−Pyrene Conjugates

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 62 publications
3
23
0
Order By: Relevance
“…S4 in the ESI †) as is the case with the UV/vis absorption data (see Table 1). The degree of a F (À0.85 to À1.01 cm À1 MPa À1 ) is also the same as the data obtained for common uorescence dyes, 54,57,59 but the quenching behavior is somewhat puzzling. In general, uorescence intensities of solutions of emissive dyes upon hydrostatic pressurization follow the Förster-Hoffmann equation [log(I F ) ¼ A log(h) + B], 27 where uorescence intensity (I F ) increases with pressureinduced viscosity (h) increasing due to the suppression of collisional deactivation by solvent, and thus increase.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…S4 in the ESI †) as is the case with the UV/vis absorption data (see Table 1). The degree of a F (À0.85 to À1.01 cm À1 MPa À1 ) is also the same as the data obtained for common uorescence dyes, 54,57,59 but the quenching behavior is somewhat puzzling. In general, uorescence intensities of solutions of emissive dyes upon hydrostatic pressurization follow the Förster-Hoffmann equation [log(I F ) ¼ A log(h) + B], 27 where uorescence intensity (I F ) increases with pressureinduced viscosity (h) increasing due to the suppression of collisional deactivation by solvent, and thus increase.…”
Section: Resultssupporting
confidence: 76%
“…21 Since the hydrostatic pressure effect on the red shi is generally observed as ca. 1 cm À1 MPa À1 in using common organic dyes, [54][55][56][57][58][59][60][61][62][63] the a A values obtained in toluene, chloroform and dichloromethane are reasonably pronounced as the general hydrostatic-pressureinduced spectral change, which means that a particular conformational change in the foldamer skeleton does not occur upon pressurization. Very interestingly, only in acetonitrile, the 0-0 absorption band is quite suppressed under low pressures, compared to the 0-1 band.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The high‐pressure apparatus was used for spectroscopic measurements. The details were reported previously [59–64] . Sapphire windows were employed for UV/vis and fluorescence spectroscopy and lifetime measurements, while birefringence‐free diamond windows were employed for circular dichroism spectroscopy.…”
Section: Methodsmentioning
confidence: 99%
“…The effects on homogeneous solutions upon hydrostatic pressurization are presented herein, rather than the solid‐state chemistry under high pressure using diamond anvil cells [57,58] . Specifically, we have so far demonstrated that emission behavior of the mechanochromic luminogens [59,60] and the chromophoric polymers, [61,62] solvatochromism of the Reichardt's dye, [63] and chiroptical properties of the hexaarylbenzenes [64] are critically regulated by hydrostatic pressure. Therefore, these research trends prompted us to construct a novel pressure‐controlled molecular recognition system.…”
Section: Introductionmentioning
confidence: 99%